Ferroptosis at the intersection of lipid metabolism and cellular signaling - Liang, Deguang; Minikes, Alexander M; Jiang, Xuejun (Molecular cell, 2022)
Ferroptosis, a newly emerged form of regulated necrotic cell death, has been demonstrated to play an important role in multiple diseases including cancer, neurodegeneration, and ischemic organ injury. Mounting evidence also suggests its potential physiological function in tumor suppression and immunity. The execution of ferroptosis is driven by iron-dependent phospholipid peroxidation. As such, the metabolism of biological lipids regulates ferroptosis via controlling phospholipid peroxidation, as well as various other cellular processes relevant to phospholipid peroxidation. In this review, we provide a comprehensive analysis by focusing on how lipid metabolism impacts the initiation, propagation, and termination of phospholipid peroxidation; how multiple signal transduction pathways communicate with ferroptosis via modulating lipid metabolism; and how such intimate cross talk of ferroptosis with lipid metabolism and related signaling pathways can be exploited for the development of rational therapeutic strategies.